Better management through evaluation : mid-term review of Structural Funds programmes: objectives 1 and 6 (1994-99). (Office for Official Publications of the European Communities, 1999)
Summary: The Mid-term review aims to ensure a more effective and efficient implementation of structural interventions delivered through Community Support Frameworks (CSFs) and Single Programming Documents (SPDs). The present report summarises the principal elements of the mid-term reviews carried out in the member states and analyses, in particular the role of the mid-term evaluations as well as the extent to which EU priorities feature in all objective 1 and 6 programmes. The following four areas are examined in the report: the overall mid-term review process; the principal findings of the mid-term evaluations; the main outcomes and adjustments made; the implications for programme delivery and priorities as well as future challenges.